Analysis of consolidation behavior of PVD-improved ground considering a varied discharge capacity. Issue 3 (8th May 2018) - Kim, Yun Tae; Nguyen, Ba-Phu; Yun, Dae-Ho
Abstract : Purpose: It is well-known that consolidation rate of prefabricated vertical drain (PVD)-installed ground is closely related to the discharge capacity of PVD, which decreases with an increase in effective stress. This paper aims to present consolidation behaviors of PVD-improved ground considering a varied discharge capacity of PVD. Design/methodology/approach: A simple equivalent vertical hydraulic conductivity (k′ ve method) was proposed in plane strain numerical analysis, in which the effect of decreased discharge capacity with depth was considered. Numerical analysis was applied to analyze field behaviors of test embankment of soft mucky deposit. Findings: Finite element method results indicated that consolidation behaviors of PVD-improved soil with a nonlinear distribution of discharge capacity with depth were in a good agreement with the observed field behaviors, compared with those with a constant discharge capacity and a linear distribution of discharge capacity. At a given time and depth, the consolidation rate in the case of discharge capacity with a nonlinear distribution is lower than that of a linear or constant distribution. Practical implications: A geotechnical engineer could use the proposed method to predict consolidation behaviors of drainage-installed ground. Originality/value: Consolidation behaviors of PVD-installed ground could be reasonably predicted by using the proposed method with considering effect of discharge capacity reduction.